Representation as limitation - a critique of Deleuze to Heidegger's ontological difference - DOI: 10.4025/actascihumansoc.v32i1.5256 - Ferronatto, Mariza Ardem Scipioni Vial (2010)
This article intends to discuss the critique of Deleuze to Heidegger, as regards the problem of representation. It presents initially the Deleuzian argument on what he calls as the dogmatic image of thought. The intention is to highlight the points that, according to the French philosopher, contaminate the philosophy of difference by Heidegger. In a second stage, it addresses the theme of ontological difference on the principle of the German philosopher. Arguments are then reported indicating possible inconsistencies in the criticism of Deleuze, which accuses Heidegger for getting rid of objective assumptions at the expense of giving subjective assumptions.